Identifying Difficulties Encountered by Indonesian EFL Learners in Oral Presentation - Kheryadi Kheryadi; Fitri Hilmiyati (Universitas Hamzanwadi, 2021)
This research investigated the most dominant issue experienced by EFL oral class presentation in their vocal class performance and identifying the extent of the students' difficulties in delivering material. The method used was the case study approach. In gaining specific data and information, the researchers collected the data by classroom observation and interviews of English students at Universitas Islam Negeri Sultan Maulana Hasanuddin Banten. The result shows that a significantly prominent matter faced by the students in doing a presentation is the explanation aspect and Self-control, getting nervous and unconfident.